Germination of Seeds and Seedling Growth of Amaranthus retroflexus L. Following Sublethal Exposure of Parent Plants to Herbicides - Qi, Yue (Sci Rep, 2017)
Herbicides have long-term effects on the vegetative parts and reproduction of plants; however, the carry-over effects of herbicides on the F1 generation of invasive plants remain unclear. The objectives of this work were to investigate the germination and growth of the F1 generation of A. retroflexus, an invasion plant, treated by sublethal herbicides. The results demonstrated that atrazine or tribenuron-methyl had carry-over effects on the F1 generation of A. retroflexus. Atrazine or tribenuron-methyl exposure during the vegetative and reproductive periods significantly inhibited the germination and growth of the F1 generation; a lower sublethal dose of atrazine or tribenuron-methyl did not weaken the inhibition of germination or growth of the F1 generation. Our results suggest that although herbicides have a carry-over inhibition effect on the F1 generation of invasive plants, they may have a more serious carry-over effect on native plants and cause changes in weed species composition and weed diversity.